The Impact of Risk-Taking attitude and Leadership Skills on Entrepreneurial Intentions of the Students of Business Administration in Punjab, Pakistan - Nafees, Muhammad; Dr. Babak Mahmood; Dr. Muhammad Farooq; Dr. Zahira Batool; Dr. Ayesha Ch. (Journal of Peace, Development and Communication, 2022)
Entrepreneurship education has gained global attention due to its significance regarding promotion of entrepreneurial culture among the communities. Boosting entrepreneurial intension has been prioritized around the world and entrepreneurship education plays key role in development of entrepreneurial mindset of the students through inculcating necessary skills. This quantitative study was designed to provide an insight of the impact of risk-taking attitude and leadership skills on entrepreneurial intentions of the target population. Students enrolled in the final semester of sixteen years of education programs of business administration in public sector universities in Punjab, Pakistan, 2022 were the target population. Data collection was done through survey method. A self-designed questionnaire was distributed among 755 respondents. The sample size was determined through sampling formula presented by Yamane (1967). The respondents were recruited from five public sector universities of Punjab through multistage sampling. The entrepreneurial intension was measured through Entrepreneurial Intension Questionnaire developed by Linan and Chen (2009). It was concluded that risk-taking attitude, and leadership skills were positively associated with the entrepreneurial mindset.